User Perception of Hydrated Website Prototype for Dehydration Prevention: Quantitative Descriptive Study - Diana Hardiyanti; Heryyanoor Heryyanoor; Melinda Restu Pertiwi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Body fluid balance or hydration status is often considered unimportant, but scientific facts show that a lack of fluids, even just one per cent, impacts cognitive decline. So, technology-based efforts are needed, such as an easily accessible website to monitor hydration status and maintain good hydration for the community. This research has described the public's perception of a hydrated website prototype for dehydration prevention Method: This research design is quantitatively descriptive, with a population of 114 respondents, using a purposive random sampling technique. The research variables, namely User perceptions of the Hydrated Website Prototype, include user skills, ease of access, appearance design, completeness of content, and application benefits. The instrument uses a questionnaire that refers to variables/sub-variables, and data analysis is done using a frequency distribution table. Result: Public perception in the good category is 99.1%, including the perception of website prototype users being hydrated to prevent dehydration based on the level of user proficiency in using a smartphone or laptop with the advanced or able-to-use category of 77.2%, ease of access in use with the easy category of 59, 6%, the appearance of the design and completeness of the contents of the website prototype in the exciting category each amounted to 64%. Meanwhile, regarding usability, the hydrated website prototype was very useful at 59.6%. Conclusion: This research concludes that user perceptions of the hydrated website prototype for dehydration prevention are good and accepted by the public.